(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines anthroponyms in the text “Baburnama” and their representation in translation. It analyzes how personal names are rendered in three well-known translations by Leyden–Erskine, A. Beveridge, and V. Texton, comparing them with the original source text. Particular attention is given to the anthroponyms “Shaikh Mazidbek,” “Umarshaikh Mirza,” “Babur Mirza,” and “Ali Mazidbek Kavchin,” which are selected for detailed analysis.